2021
DOI: 10.3390/ijerph19010157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Family Practice Contract Services on the Perceived Quality of Primary Care among Patients with Multimorbidity: A Cross-Sectional Study in Guangdong, China

Abstract: Family practice contract services, an important primary-care reform policy for improving primary healthcare quality in China, incorporate patients with multiple chronic conditions into the priority coverage groups and focus on their management. This study aims to explore the family practice contract services’ effectiveness in improving the quality of primary care experienced by this population. A cross-sectional study using a three-stage sampling was conducted from January to March 2019 in Guangdong, China. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…The second layer of the decision tree consisted of age and whether the patient had an existing relationship with a family doctor, indicating that both were important factors influencing a patient's choice of healthcare institutions. Our results thus showed that the older the patient with comorbidities, the more likely they tended to prefer primary healthcare institutions for medical treatment, consistent with the findings of many related studies [ 13 , 14 ]. Patients in older age experience a decline in physical function, and as the number of illnesses increases, the frequency of various minor physical discomforts also increases, leading to an increased number of medical visits.…”
Section: Discussionsupporting
confidence: 91%
“…The second layer of the decision tree consisted of age and whether the patient had an existing relationship with a family doctor, indicating that both were important factors influencing a patient's choice of healthcare institutions. Our results thus showed that the older the patient with comorbidities, the more likely they tended to prefer primary healthcare institutions for medical treatment, consistent with the findings of many related studies [ 13 , 14 ]. Patients in older age experience a decline in physical function, and as the number of illnesses increases, the frequency of various minor physical discomforts also increases, leading to an increased number of medical visits.…”
Section: Discussionsupporting
confidence: 91%
“…First, regarding health service utilisation, a large body of literature has focused on the reform process of health service systems, influencing factors of health service utilisation inequity, and the connection between MCCs and health service utilisation, cost and mortality 13 26–28. Second, in terms of vertical equity in health service utilisation, few studies have longitudinally measured and summarised health service demand and utilisation equity among MCCs patients, mostly using cross-sectional data or an overview of the influencing factors and severity of MCCs 4 29 30. Third, in terms of horizontal equity in health service utilisation, abundant research has considered objective differences, such as gender and age, while placing greater emphasis on the inequity stemming from controllable socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%